Hydrodynamical transport structure and lagrangian connectivity of circulations in the Pearl River Estuary - Chu, Nanyang; Liu, Guangliang; Xu, Jie; Yao, Peng; Du, Yan; Liu, Zhiqiang; Cai, Zhongya (Frontiers in Marine Science, 2022)
Using a 3D hydrodynamic model, this study explored the seasonal hydrodynamic transport structure in the Pearl River Estuary and illustrated the intrinsic connectivity under multiscale motions from a Lagrangian perspective. Generally, the surface Lagrangian residual current (UL) is uniformly southwestward/southeastward in summer/winter, with a stronger intensity in the lower estuary. The bottom UL features in the southeastward direction in the upper estuary and northwest direction in the lower estuary. The fluvial-tide interaction line advances southeastward and northwestward in summer and winter, respectively. The UL captured the major transport processes and was in good agreement with the mean surface sediment transport patterns. In the transition region between Lantau Island and Neilingding Island, where is largely affected by the interaction between the periodic tidal current and river discharge, the spatially averaged UL showed intensified intra-tidal variations and had a larger difference with the locally temporally averaged Eulerian residual current. Remarkable Lagrangian coherent structures (LCSs) that illustrated the transport paths and transport convergence regions were identified, which are generally consistent with the bottom sediment depocenters. Based on the LCSs and connectivity matrix, it was revealed that a distinct barrier between the western and eastern estuaries existed, which was weakened by the strong river discharge during summer. Two convergence regions near the Macau and Hong Kong waters were identified, where the sediment and pollutants easily settled. The study demonstrated the importance of the Lagrangian view in understanding the hydrodynamic process and transport structure in the estuary-shelf regions.